Reconstruction of the Spatial Law of the Sacred Area in Bali Based on Local Wisdom and Pancasila - Wibawa, I Putu Sastra (Law Research Review Quarterly, 2016)
This study aims to find out the reasons for the spatial planning law of the holy sites in Bali and need to be reconstructed and 2) the process of reconstructing the spatial planning law in Bali based on local wisdom and Pancasila. The discussion uses the constructivist paradigm with a socio-legal approach. As a knife in analyzing the discussion using theories and concepts of the rule of law, legal hermeneutics, legal system theory, legal pluralism, and progressive law. As for the results of the discussion, among others: First, the reason for the need for reconstruction of the spatial planning law of the holy sites in Bali based on several factors, including: factors, politics, law, culture, economics and ideology. Second, there are several stages of reconstruction, including: the preliminary, the formation, the conflict, and the development that will result in the regulation of the spatial structure of the shrine area which is not rigid, adjusted to the conditions and characteristics of each region in accordance with the principles of local wisdom based on the ideology values ​​of Pancasila.